2020
DOI: 10.1088/1755-1315/570/3/032031
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization in hydraulic fracturing of granite specimens based on DIC method

Abstract: Hydraulic fracturing is a crucial and widely-used technology in shale gas exploitation and enhanced geothermal systems, while the fundamental mechanisms of hydraulic fracturing are not comprehensively understood. This paper aims to promote the understanding of strain localization in hydraulic fracturing of granite specimens based on digital image correlation (DIC) method. Through a specially designed pressure enclosure, the hydraulic fracturing processes were captured by a high-speed camera. The strain localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on DIC analysis, obvious strain localization phenomena was observed before the expansion of the hydraulically induced cracks [11,12], as shown in figure 5(a). Before failure, a clear strain localization zone appeared at the crack tip and gradually extended towards both ends of the sample over time, showing progressive damage evolution characteristics.…”
Section: Relationship Between Crack Evolution and Mineral Particle Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on DIC analysis, obvious strain localization phenomena was observed before the expansion of the hydraulically induced cracks [11,12], as shown in figure 5(a). Before failure, a clear strain localization zone appeared at the crack tip and gradually extended towards both ends of the sample over time, showing progressive damage evolution characteristics.…”
Section: Relationship Between Crack Evolution and Mineral Particle Di...mentioning
confidence: 99%
“…This facilitated the successful visualization of hydraulically induced crack propagation experiments, achieving high-precision displacement and strain fields using DIC analysis. Zhao et al [11] conducted experimental studies on fast granite and reported strain localization phenomena [12] and crack merging patterns [11] in hydraulically induced crack propagation, gaining a better understanding of the mechanism. Niu [9] adopted a "two rigid and one flexible" approach, realized true triaxial loading on a conventional biaxial testing machine, and conducted several experiments to study the crack propagation pattern and its influencing factors under true triaxial loading in hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%